2014
DOI: 10.1093/mnras/stu1292
|View full text |Cite
|
Sign up to set email alerts
|

Gas and stellar motions and observational signatures of corotating spiral arms

Abstract: We have observed a snapshot of our N-body/Smoothed Particle Hydrodynamics simulation of a Milky Way-sized barred spiral galaxy in a similar way to how we can observe the Milky Way. The simulated galaxy shows a co-rotating spiral arm, i.e. the spiral arm rotates with the same speed as the circular speed. We observed the rotation and radial velocities of the gas and stars as a function of the distance from our assumed location of the observer at the three lines of sight on the disc plane, (l, b) = (90, 0), (120,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 93 publications
8
90
0
Order By: Relevance
“…This suggests that the observed peculiar motions can be explained by either a combination of a bar and transient, co-rotating spiral arms (Grand et al 2012b;Kawata et al 2014) or the bar component only as found by (Bovy et al 2015, B15). In contrast, the observed power spectrum cannot be explained by the stellar motion induced by the density wave-like spiral arms in test particle simulations F14 and M15.…”
Section: Resultsmentioning
confidence: 67%
“…This suggests that the observed peculiar motions can be explained by either a combination of a bar and transient, co-rotating spiral arms (Grand et al 2012b;Kawata et al 2014) or the bar component only as found by (Bovy et al 2015, B15). In contrast, the observed power spectrum cannot be explained by the stellar motion induced by the density wave-like spiral arms in test particle simulations F14 and M15.…”
Section: Resultsmentioning
confidence: 67%
“…2. In contrast to the STEADY model, in the DYNAMIC model, the SPH particle trajectories that are overlaid on the x-y map of the gas show that gas and stars fall into the spiral arm from both sides, rather than from just one side (see also Dobbs & Bonnell 2008;Wada et al 2011;Kawata et al 2014) 5 . The left panels of Fig.…”
Section: Gas Flows and Velocity Patterns Around Spiral Armsmentioning
confidence: 95%
“…First, in numerical simulations, the study of asymmetric motions has been shown to be powerful to understand the response of gaseous or stellar particles to barred, spiral, or lopsided potentials, (e.g., among many articles, Combes & Sanders 1981;Athanassoula 1992;Wada 1994;Sellwood & Binney 2002;Maciejewski 2004;Bournaud et al 2005;Quillen et al 2011;Grand et al 2012;Minchev et al 2012;Renaud et al 2013). For instance, simulations are helpful to study the radial migration of stellar particles through spiral arms and the dynamical effects of the spiral structure on radial and rotational velocities to predict signatures to be detected by kinematical samples of Galactic disk stars (Kawata et al 2014b). Simulations can also depict the strong influence of the dynamics in a stellar bar on velocities across and along the bar axes in order to analyze the survival and merging of gaseous clouds and their implication on star formation .…”
Section: Comparison With Previous Work and Numerical Simulationsmentioning
confidence: 99%
“…These offsets are caused by particles that are losing (or gaining, respectively) angular momentum (see also Fig. 4 of Kawata et al 2014b), and that thus have nonmarginal radial motions. The circular motion is therefore altered by noncircular motions at these locations.…”
Section: Comparison With Previous Work and Numerical Simulationsmentioning
confidence: 99%